Baseline survey of CCAFS sites: monitoring and planning for climate-smart interventions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Baseline surveys, designed by CCAFS, were carried out as part of the process in setting up Climate-Smart Villages in the Indo-Gangetic Plains in South Asia. This survey aimed to provide baseline information at the village level about socio-economic indicators, natural resource utilisation, organisational landscapes, information networks for weather and agricultural information and mitigation baseline information. This information can be compared across sites and monitored over time. The surveys also provide important information for planning and implementing climate-smart interventions in the CCAFS sites.